Teias de saberes nas redes de relações : educação nas escolas sinodais - Goldmeyer, Marguit Carmem (2008)
The central theme of this thesis is the teaching-learning process and the networks of relationships that are woven within the Rede Sinodal de Educação school network. A number of threads make up this web of relationships and insights. Knowledge is the main one, the thread that lends consistency to the others and permeates, in one way or another, all pedagogic actions. Along with it comes the thread of dialogue, which in turn is made up of many other important strands: respect, responsibility, commitment, search, acceptance and love. The dialogue thread is held in someone's hands; through this person it reaches others, fostering communion and sharing among people and groups. Within education we perceive a number of threads involved in weaving the web of insights. Many people are responsible for the weaving, which explains the beauty of its pattern, but at times also turns it into an unmanageable tangle of threads. Nevertheless, when the goal is clear: an education that lends meaning to lives, based on knowledge that liberates and brings about change, any knot [in Portuguese: nó] can be undone and transformed in learning through the action taken by "us" [in Portuguese: nós], the people involved. This paper aims at making that reflective thread much more present in everyday school life. The research was carried out with teachers from the network of schools in Brazil called the Rede Sinodal de Educação. As these teachers live within this net and weave it on a daily basis, the option was made to use the metaphor of the net and the web [in Portuguese, 'rede' stands for both words] and tie in a few other related words with a figurative meaning. Within this web of insights, woven in the network of relationships, many threads of experience, wisdom, learning and teaching are found: there is life pulsing in it, which can serve as inspiration and reflection for the moment that Brazilian education is currently going through. Individuality, love, knowledge and dialogue may be the inspiring threads for a more humane, just and solidary education.